Evaluation of Biological Effective Dose in Gamma Knife Staged Stereotactic Radiosurgery for Large Brain Metastases - Cui, Taoran; Weiner, Joseph; Danish, Shabbar; Chundury, Anupama; Ohri, Nisha; Yue, Ning; Wang, Xiao; Nie, Ke (Frontiers in Oncology, 2022)
Objective Gamma knife (GK) staged stereotactic radiosurgery (Staged-SRS) has become an effective treatment option for large brain metastases (BMs); however, it has been challenging to evaluate the total dose because of tumor shrinkage between two staged sessions. This study aims to evaluate total biological effective dose (BED) in Staged-SRS, and to compare the BED with those in single-fraction SRS (SF-SRS) and hypo-fractionated SRS (HF-SRS). Methods Patients treated with GK Staged-SRS at a single institution were retrospectively included. The dose delivered in two sessions of Staged-SRS was summed using the deformable image registration. Each patient was replanned for SF-SRS and HF-SRS. The total BEDs were computed using the linear-quadratic model. Tumor BED98% and brain V84Gy2, equivalent to V12Gy in SF-SRS, were compared between SF-SRS, HF-SRS, and Staged-SRS plans with the Wilcoxon test. Results Twelve patients with 24 BMs treated with GK Staged-SRS were identified. We observed significant differences (p < 0.05) in tumor BED98% but comparable brain V84Gy2 (p = 0.677) between the Staged-SRS and SF-SRS plans. No dosimetric advantages of Staged-SRS over HF-SRS were observed. Tumor BED98% in the HF-SRS plans were significantly higher than those in the Staged-SRS plans (p < 0.05). Despite the larger PTVs, brain V84Gy2 in the HF-SRS plans remained lower (p < 0.05). Conclusion We presented an approach to calculate the composite BEDs delivered to both tumor and normal brain tissue in Staged-SRS. Compared to SF-SRS, Staged-SRS delivers a higher dose to tumor but maintains a comparable dose to normal brain tissue. Our results did not show any dosimetric advantages of Staged-SRS over HF-SRS.